2019
DOI: 10.1096/fj.201901820r
|View full text |Cite
|
Sign up to set email alerts
|

AMPK β1 activation suppresses antipsychotic‐induced hyperglycemia in mice

Abstract: Olanzapine (OLZ) is a second-generation antipsychotic that is used to treat schizophrenia but also causes acute hyperglycemia. This study aimed to determine if the ablation of AMPK b1-containing complexes potentiates acute OLZ-induced metabolic dysfunction and if the activation of AMPK b1 suppresses these effects. Female AMPK b1 2/2 or wild-type (WT) control mice were treated with OLZ, and changes in blood glucose, serum and liver metabolites, whole-body fuel oxidation, and pyruvate-induced increases in blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…The current doses of drugs were chosen to be consistent with prior studies that have observed metabolic effects of risperidone in both our laboratory and by other groups [36,37,57], and at preclinical doses comparable to those observed with other antipsychotic drugs which exert effects of a similar magnitude to those noted in humans [45]. The present experimental procedures provide complementary techniques to assess the overall metabolic side-effects of antipsychotic drugs, as we and multiple other groups have demonstrated previously [39][40][41][42][43][44]68,69]. Fasting glucose levels are the simplest and most common way used to detect hyperglycemia in humans (and animals), but can be prone to error in a significant proportion of individuals [70].…”
Section: Plos Onementioning
confidence: 82%
See 1 more Smart Citation
“…The current doses of drugs were chosen to be consistent with prior studies that have observed metabolic effects of risperidone in both our laboratory and by other groups [36,37,57], and at preclinical doses comparable to those observed with other antipsychotic drugs which exert effects of a similar magnitude to those noted in humans [45]. The present experimental procedures provide complementary techniques to assess the overall metabolic side-effects of antipsychotic drugs, as we and multiple other groups have demonstrated previously [39][40][41][42][43][44]68,69]. Fasting glucose levels are the simplest and most common way used to detect hyperglycemia in humans (and animals), but can be prone to error in a significant proportion of individuals [70].…”
Section: Plos Onementioning
confidence: 82%
“…To this end, animal models of antipsychotic-induced metabolic side-effects have been helpful and informative in characterizing the acute metabolic effects of antipsychotics [32]. These studies have confirmed that treatment with most second generation antipsychotics can cause glucose intolerance and insulin resistance, often within minutes [33][34][35][36][37][38][39][40][41][42][43][44]-effects that have been confirmed in non-psychiatric human subjects [45][46][47] including in a recent metaanalysis [48]. In current clinical practice, both paliperidone and the parent drug risperidone are often prescribed interchangeably [49], as they have a similar therapeutic profile and both exist in depot formulations [50][51][52].…”
Section: Introductionmentioning
confidence: 88%
“…The use of preclinical paradigms offers the additional benefit of helping to disentangle the multifactorial causes of metabolic dysregulation in psychiatric illness, where variables such as diet, exercise, and drug use can all contribute to cardiometabolic dysregulation (25)(26)(27). Fortunately, the past 10-15 years has seen significant advances in animal models of the metabolic side-effects of antipsychotic drugs (28), which have demonstrated that many of these compounds cause acute glucose dysregulation and insulin resistance independent of weight gain (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…A colony of AMPKβ1 knockout mice (AMPKβ1 −/− ) was generated and maintained as previously described. 27,28 Genotypes were determined for all mice from ear notches and subsequently confirmed by immunoblot. Experiments were performed on male mice between 10 and 18 weeks of age with the approval of the University of Guelph Animal Care Committee in compliance with the guide for the care and use of laboratory animals and the Canadian Council on Animal Care.…”
Section: Micementioning
confidence: 99%
“…For some experiments, mice were fed a high‐fat diet for 24 weeks (60% kcal from fat, #D12492; Research Diets, New Brunswick, NJ USA). A colony of AMPKβ1 knockout mice (AMPKβ1 −/− ) was generated and maintained as previously described 27,28 . Genotypes were determined for all mice from ear notches and subsequently confirmed by immunoblot.…”
Section: Introductionmentioning
confidence: 99%